COMPARING THE POLITICAL TRUST AND CIVIC POLITICAL CULTURE OF DEMOCRACY OR AUTHORITARIAN IN ASIAN COUNTRIES - Yang, Hsiu-wen (International Journal of Research -GRANTHAALAYAH, 2021)
The political trust of the people is essential for the consolidation of the regime, but it has not been discussed whether the democratic or authoritarian system is more consolidated. This article uses the Asian Democracy Dynamics Survey of 2010 to divide 11 countries into the system of democracy, excessive democracy and autocracy, and autocracy according to the Polity IV index. It will test the people’s political trust in these three different political systems, and try to explain the differences from the "cultural perspective" and "citizen classification." The cultural perspective is divided into authoritarianism, traditionalism, collectivism, and Confucian which belongs to the specific political culture in Asia. This paper created the concept of "accepted and rejected" citizenship. Studies have found that the more authoritarian the country, the higher the trust of the people, and it’s not easy to change the original regime. In addition to the traditional view, those who do hold culturally authoritative, collective, and Confucian views have high political trust and trust the government to take full responsibility. People have a higher degree of trust in their government, which is the hidden reason that may cause the authoritarian or transitional regime to fail to transform into a democratic regime.